Effect of Microbial Fertiliser on Salt Ions Content and Growth of Lycium barbarum in Saline Soil under Brackish Water Irrigation - ZHAI Jie; YANG Shuqing; LIU Yue; CHEN Yu (Shuitu Baochi Xuebao)
［Objective］ To investigate the effects of microbial fertilizer application under brackish water irrigation on salt ion content in saline soil and on the growth of Lycium barbarum, as well as to elucidate the relationship between soil salt ions and Lycium barbarum growth indices. ［Methods］ A series of field experiments were conducted on moderately saline soils in the Hetao Irrigation Area. Four different application rates of microbial fertilizer were tested under brackish water irrigation conditions: F1 (45 kg/hm2), F2 (75 kg/hm2), F3 (105 kg/hm2), and F0 (0 kg/hm2, as control). ［Results］ Soil salt ion levels declined with increased microbial fertilizer application. Notably, compared to F0, the F3 treatment significantly reduced Na+, K+ and Cl- levels by 49.22%, 40.20%, and 47.80%, respectively, throughout the reproductive period (p<0.05). Additionally, plant height, ground diameter, canopy width, and new branch growth rate in LBP significantly increased with higher microbial fertilizer levels (p<0.05), with the F2 treatment yielding the greatest improvements. During the flowering stage—a period highly sensitive to growth—the plant height growth rate in F2 exceeded that of F0 by 3.27%. In the spring growth period, the growth rates of plant height, canopy width, and new branches all peaked, while the growth rate of ground diameter reached its highest in the fruit expansion stage. The Lycium barbarun yield in the F2 treatment was 46.33% higher than that in F0 (p<0.05), with a fertilizer partial productivity of 0.61 kg/kg. Correlation analysis indicated a negative relationship between soil Na+, K+ and Cl- concentrations and Lycium barbarum growth parameters. ［Conclusion］ In summary, to optimize soil conditions and promote Lycium barbarum growth in saline soils under brackish water irrigation in the Hetao Irrigation District, a microbial fertilizer application rate of 75~105 kg/hm2 is recommended.